Normative spatiotemporal and ground reaction force data for female and male sprinting - Nagahara, R. (Journal of Sports Sciences, 2023)
This study aimed to demonstrate the differences in spatiotemporal and ground reaction force (GRF) variables during overground sprinting between performance levels for female and male sprinters with providing normative data during the entire acceleration phase. Forty-four female and 102 male sprinters performed 60-m sprints, during which the spatiotemporal and GRF variables were obtained using a long force platform system. Female and male sprinters were each allocated into four groups based on their maximal speed (7.5-9.5 m/s and 8.5-10.5 m/s, respectively) with 0.5 m/s intervals, and average values for 50-m distance were calculated. Using the GRF data, normative data for four groups of female and male sprinters were successfully obtained. For female sprinters using average values of all steps, there were differences between performance levels for step frequency (SF) and support time (ST), all impulses, and all mean forces. For male sprinters using average values of all steps, there were differences between performance levels for SF, ST and flight time, all impulses except for braking impulse, and all of the mean forces. The normative data indicate that most of the spatiotemporal and GRF variables may be changed, particularly increasing SF and propulsive force, when sprint performance is improved.